β2GP1, Anti-β2GP1 Antibodies and Platelets: Key Players in the Antiphospholipid Syndrome - Yik C. Ho; Kiran D. K. Ahuja; Heinrich Körner; Murray J. Adams (Antibodies, 2016)
Anti-beta 2 glycoprotein 1 (anti-β2GP1) antibodies are commonly found in patients with autoimmune diseases such as the antiphospholipid syndrome (APS) and systemic lupus erythematosus (SLE). Their presence is highly associated with increased risk of vascular thrombosis and/or recurrent pregnancy-related complications. Although they are a subtype of anti-phospholipid (APL) antibody, anti-β2GP1 antibodies form complexes with β2GP1 before binding to different receptors associated with anionic phospholipids on structures such as platelets and endothelial cells. β2GP1 consists of five short consensus repeat termed “sushi” domains. It has three interchangeable conformations with a cryptic epitope at domain 1 within the molecule. Anti-β2GP1 antibodies against this cryptic epitope are referred to as ‘type A’ antibodies, and have been suggested to be more strongly associated with both vascular and obstetric complications. In contrast, ‘type B’ antibodies, directed against other domains of β2GP1, are more likely to be benign antibodies found in asymptomatic patients and healthy individuals. Although the interactions between anti-β2GP1 antibodies, β2GP1, and platelets have been investigated, the actual targeted metabolic pathway(s) and/or receptor(s) involved remain to be clearly elucidated. This review will discuss the current understanding of the interaction between anti-β2GP1 antibodies and β2GP1, with platelet receptors and associated signalling pathways.